(untitled) (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2023)
Sprachsensibilität gilt seit längerer Zeit als ein Qualitätsmerkmal für Unterricht. Mit Blick auf die Bedingungen des Aufwachsens der Kinder und Jugendlichen ist sie jedoch unterbestimmt, wenn sie ausschließlich Schüler*innen mit Migrationshintergrund fokussiert. Im Beitrag wird deshalb Milieusensibilität als Erweiterung von Sprachsensibilität vorgeschlagen. Diese greift die Bedingungen des Aufwachsens auf und nutzt sie reflektiert im Unterricht. Durch eine umfassendere Berücksichtigung der realen Situation aller Schüler*innen sollen die Chancen auf nachschulische Teilhabe erhöht werden. This article discusses the importance of sensitivity to language in teaching and proposes an extension to this concept through the introduction of ‘milieu sensitivity’. The article suggests that while sensitivity to language has been recognized as a quality criterion for teaching, it has often only focused on students with a migration background, without fully understanding the conditions of growing up and socialization of all children and young people. By taking into account these conditions and reflecting on them, the concept of milieu sensitivity can promote a more comprehensive understanding of the real-life situation. We argue that by promoting inclusivity and equitable learning outcomes for all students through this approach, post-school participation can be increased.